Caribbean Digital Library Initiatives in the 21st Century: the Digital Library of the Caribbean (dLOC) - Renwick, Shamin (Manchester University Press, 2011)
As a result of evolving Information and Communication Technologies (ICTs), digital libraries which allow for greater accessibility and preservation of information have been started in earnest in the last decade or two. Several digital initiatives have been implemented recently in the Caribbean, about 40 countries with diverse history, culture, language, religious and socio-cultural backgrounds. Affordable technology and infrastructure, networking and cataloguing expertise, enduring collaboration, workable governance mechanisms, intellectual property/copyright measures, adequate financing and ongoing an training are imperative for the sustainability of these projects. One of the more well-known and well-regarded is the trilingual Digital Library of the Caribbean (dLOC) which was established to provide greater visibility and accessibility to Caribbean materials in order to further Caribbean studies. Initial vision for the dLOC was outlined in 2004 at the Association of Caribbean University, Institutional and Research Libraries conference in Trinidad and Tobago. After successfully obtaining US Federal funding, four US Libraries and five Caribbean partners established a rather unique model of collaborative governance and collection building. With leadership, extensive technological development and preservation activities by several Florida Universities, the dLOC has provided support and training to its Caribbean partners and together have met many technological, intellectual and ethical challenges to Caribbean digital initiatives successfully to produce a user-friendly interface with extensive search functionality. The dLOC, now a multi-institutional project with international usage, appears to have implemented sustainable practices; has proven to be trustworthy, flexible, responsive, adaptable, proactive and empowering; and has demonstrated goodwill through humanitarian efforts.
Keywords: digital libraries, Caribbean, dLOC